O desejo na psicanálise: do objeto do desejo ao objeto causa de desejo - Araújo, Tatiely Pereira de (2018)
In the course of this dissertation, it was possible to investigate how the notion of desire as an axial is used to articulate the foundations of psychoanalysis. For this, the origin of the subject's conception in modern philosophy and the construction / deconstruction of this notion by Freud were first worked on, and then revisited in a second moment, central texts of the Freudian work in order to understand how Freud articulated the the notion of unconscious desire, to finally discuss how Lacan took the notion of desire as central to the structuring of the subject's field. This path has led us to realize that the subject can only emerge in its relation to object a, while it operates through dialectics, taken here as demand / desire and alienation / separation. These dialectics were only possible to be articulated in Lacan's passage from the object of desire to the object of desire, thus marking the central point of this writing.